Mass Photometry of Membrane Proteins - Olerinyova, A; Sonn-Segev, A; Gault, J; Eichmann, C; Schimpf, J; Kopf, A H; Rudden, L S P; Ashkinadze, D; Bomba, R; Frey, L; Greenwald, J; Degiacomi, M T; et al. (University of Oxford, 2020)
Here, we explore the application of mass photometry (MP) to integral membrane proteins and membrane mimetic systems at the single particle level. We apply MP to amphipathic vehicles, such as detergents and amphipols, as well as to lipid and native nanodiscs, characterizing the particle size, sample purity and heterogeneity. Using methods established for cryogenic electron microscopy, we eliminate detergent background, enabling high-resolution studies of membrane protein structure and interactions. We find evidence that, when extracted from native membranes using native styrene-maleic acid nanodiscs, the potassium channel KcsA is present as a dimer of tetramers – in contrast to results obtained using detergent purification. Finally, using lipid nanodiscs, we show that MP can help distinguish between functional and non-functional nanodisc assemblies, as well as determine the critical factors for lipid nanodisc formation.